Peran Roh Kudus dalam Konseling - Nurlela Syafrian Oematan; Yeyen Darmadi; Sardi Samjar; Simon Simare Mare; Stefanus Alpha Yani Kristiono (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2024)
Christian believes that the presence of the Holy Spirit as real evidence of Jesus’s promise to His people. But, almost counselor Christians today haven’t a wonderful experience of the guidance of the Holy Spirit so that the counselee would not find the right answer for his problem. Wheraas a counselor who is guided by Him will overcome the problem and get a nice advice from the Holy Spirit. This study aim to answer the question, what is the role of The Holy Spirit in pastoral counseling in fulfilling the God’s word? This research is a library research which apply descriptive analysis method with the Bible as the main source and other literature of Holy Spirit. The conclusion of this research is ,first, The Holy Spirit give good calmness and peacefulness so that people feel in their soul especially counselor and counselee, Second, The Holy Spirit gives the counselor wisdom and understanding to know all the problem of human life and convey to the people who plays as counselee. Third, the Holy Spirit lead the counselor to push the counselee back to the truth of God’s word.